the The Effects Of Streching And Strengthening Exercise On Motor Cycle Gros Inchildren With Cerebral Palsy Spastic Type At Memorial Murni Teguh Hospital Medan 2023 - Tuty Swarni Sinaga (International Journal of Health Engineering and Technology, 2024)
Cerebral palsy (CP)Congenital malformasi: a condition of weakness of the extremities which results in distruption of the child's growth and development. The cause of cerebral palsy is the result of brain damage or brain defects which most often occur when a person is still in the womb or after birth, although there are several cases that experience CP is not congenital. This condition of congenital malformation has an unstable movement coordination system.floppiness or stiffness of the limbs,the emergence of abnormal movement ,poor balance,or several combination of the signs that have been mentioned. Congenital malformation affects the motor and function capacity system. The aim of this is to find out that there is a stretching effec and strengthening exercise on gross motor skills in spastic type cerebral palsy. The type of research uses a quasi experiment with pre and post test design. The research sample is 7 children with spastic type cerebral palsy at Murni Teguh Hospital in Medan who meet the research criteria. The level of spasticity was measured by observation using the Mas method (Muscle Ashwort scale) with repeated measurements, before and after treatment In research, data analysis this study used is T.Test (t test).